Negosiasi Hadis dengan Tradisi Pembacaan Berzanji dalam Prosesi Pernikahan Masyarakat Bugis - Eti Kamala Sari; Azka Zahid Putra; Luqmanul Hakim (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study explores the negotiation between hadith and the tradition of reciting Berzanji in the wedding ceremonies of the Bugis community in Sungai Raya Village, Tanjung Jabung Timur Regency. While Berzanji is commonly performed during the celebration of the Prophet Muhammad’s birthday (Mawlid), in this community it has become an integral part of wedding rituals. This phenomenon raises questions regarding its compatibility with Islamic teachings, particularly from the perspective of hadith. The research employs a qualitative approach using historical-causal and structural analysis to examine how the community interprets hadith and incorporates it into socio-religious practices. The findings indicate that Berzanji is viewed as a spiritual medium to strengthen love for the Prophet and to promote Islamic values during a sacred life event. Rather than being considered a deviation, it is understood as a contextual religious expression. This reflects a form of social ijtihad, where hadith is interpreted not merely textually but in harmony with local cultural and spiritual values, preserving Bugis identity in the Jambi diaspora.